PENGUATAN DAYA SAING PRODUK LOKAL MELALUI PELATIHAN P-IRT DAN DIGITAL MARKETING DI BALAI DESA GONDEK UNTUK KEMANDIRIAN USAHA - Yuniep Mujiati , Suaidah; Mohammad Fatoni , Yahya (STIE PGRI Dewantara Jombang, 2025)
P-IRT and Digital Marketing Training at Gondek Village Hall is an initiative to increase the competitiveness of local products and encourage community business independence. Initial conditions showed that many MSMEs in this village still face obstacles in business licensing and digital marketing strategies. Lack of understanding of P-IRT certification and the use of digital platforms makes local products less competitive in the wider market. As a solution, this program includes socialization and training in making P-IRT to increase awareness and understanding of business actors about the importance of product legality. In addition, digital marketing seminars focused on optimizing marketplace platforms and social media as marketing tools. This activity includes technical guidance on branding, product photos, and digital-based marketing strategies to increase market reach. The results of this training show an increase in the number of MSMEs applying for P-IRT, as well as increased skills in utilizing digital marketing. Local products are starting to be known more widely through digital platforms, supporting community economic growth. The follow-up plan includes monitoring and further assistance to ensure the sustainability of the program's impact.